2019
DOI: 10.1111/jcal.12414
|View full text |Cite
|
Sign up to set email alerts
|

Problematic internet use and study motivation in higher education

Abstract: The current study explored the relationship between problematic internet use (PIU) and motivation to learn, and examined psychological and social factors mediating this relationship. Two hundred and eighty-five students in an Italian University were recruited for the current study. There was a negative relationship between PIU and motivation to study: a negative impact on learning strategies, meaning that the students found it harder to organise their learning productively; and PIU also positively associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 39 publications
(47 reference statements)
3
23
0
5
Order By: Relevance
“…In sum, the results indicated that, to a greater extent, risks associated with the Internet, such as the consumption of pornography and young people's addiction to video games and the behavioral disorders associated with them, obtained a considerable density of publication, and therefore these are risks that affect society today [23,24]. In a similar vein, the analysis of the relationship between issues through the Jaccard index allowed us to discern relevant connections between issues, as was the case with the one maintained between "prevalence-prevalence-depression-adolescent", "addiction-behavior-addiction-adolescent", or "online-loneliness-self-esteem".…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In sum, the results indicated that, to a greater extent, risks associated with the Internet, such as the consumption of pornography and young people's addiction to video games and the behavioral disorders associated with them, obtained a considerable density of publication, and therefore these are risks that affect society today [23,24]. In a similar vein, the analysis of the relationship between issues through the Jaccard index allowed us to discern relevant connections between issues, as was the case with the one maintained between "prevalence-prevalence-depression-adolescent", "addiction-behavior-addiction-adolescent", or "online-loneliness-self-esteem".…”
Section: Discussionmentioning
confidence: 93%
“…At present, students, regardless of their educational stage, are one of the groups most closely related to everything related to ICT and its use for different purposes, such as socialization or proper academic development [22]. Experts on the field state that those students who use the Internet for purposes that go beyond simple socialization through the different social networks and video games have a better level with regard to problems related to the use of this technology [23]. The exclusive use of these media for playful or socializing purposes without an educational perspective or previous training in the correct use and handling can lead to problems such as sexting [24], cyberbullying [25], or video game addiction [26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, students who tend to use the Internet for more general rather than academic purposes might have lower academic performance (Kim et al, 2017), but problematic Internet use might also be related to lower motivation to learn (Truzoli et al, 2019). Such relationships indicate that digital engagement might differ for students with distinct motivational profiles.…”
Section: Orientationsmentioning
confidence: 99%
“…Finally, we point out that the use of Internet, in addition to being an opportunity (e.g., online interactions will limit the detrimental effects of social isolation), can represent a coping strategy to face difficulties (Romano et al, 2013) which can however have negative consequences, how to promote the development of psychiatric symptoms (Pfefferbaum & North, 2020) and lead to excessive time spent on social networks (Truzoli et al, 2020; Viganò et al, 2020).…”
mentioning
confidence: 98%